ROOT CAUSE ANALYSIS AND PROPOSED IMPROVEMENT OF OUTBOUND LOGISTICS PERFORMANCE IN PERTAMINA PATRA NIAGA - Candrasmurti, Awindya; Yudoko, Gatot (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
PT Pertamina Patra Niaga represents a prominent Indonesian national enterprise specializing in the distribution of industrial fuels. Despite the widespread presence of gas stations nationwide, the stability of gasoline supply in Indonesia encounters challenges, primarily stemming from persistent issues related to fuel shortages. These challenges are influenced by factors such as transportation constraints and inefficiencies in distribution processes. This study is focusing on issues related to the non-attainment of the MS2 Compliance target due to delays in delivery times associated with outbound logistics performance. The research especially seeking to identify factors influencing the MS2 Compliance value at Integrated Terminal Surabaya and proposing initiatives for enhancing outbound logistic performance. The conceptual framework employed in this research delineates the supply chain design, with a specific emphasis on outbound logistics aimed at efficiently delivering final products to retailers. This strategy aligns with achieving a responsive supply chain by improving outbound logistic performance, with tank trucks serving as the primary equipment for transportation. The Root Cause Analysis was conducted using Ishikawa fishbone. The results reveal four main contributing factors: method, environment, human, and equipment considerations. For method factors, the analysis employs a heuristic method, specifically